Apocalypse delayed : the story of Jehovah's Witnesses - Penton, M. James, 1932- (Toronto ; Buffalo : University of Toronto Press, 2015)
"Since 1876, Jehovah's Witnesses have believed that they are living in the last days of the present world. Charles T. Russell, their founder, advised his followers that members of Christ's church would be raptured in 1878, and by 1914 Christ would destroy the nations and establish his kingdom on earth. The first prophecy was not fulfilled, but the outbreak of the First World War lent some credibility to the second. Ever since that time, Jehovah's Witnesses have been predicting that the world would end "shortly." Their numbers have grown to many millions in over two hundred countries. They distribute a billion pieces of literature annually, and continue to anticipate the end of the world. For almost thirty years, M. James Penton's Apocalypse Delayed has been the definitive scholarly study of this religious movement. As a former member of the sect, Penton offers a comprehensive overview of the Jehovah's Witnesses. His book is divided into three parts, each presenting the Witnesses' story in a different context: historical, doctrinal, and sociological. Some of the issues he discusses are known to the general public, such as the sect's opposition to military service and blood transfusions. Others involve internal controversies, including political control of the organization and the handling of dissent within the ranks. Thoroughly revised, the third edition of Penton's classic text includes substantial new information on the sources of Russell's theology and on the church's early leaders ..."--
pt. II. Concepts and doctrines -- 8. Bases of doctrinal authority -- The Faithful and the Discreet Slave -- Progressive revelation -- Natural theology and the Bible -- Biblical interpretation -- Philosophy of history -- 9. Major doctrines -- Theology -- Christology and soteriology -- Covenantal relationships -- Spirit creatures -- The nature of humankind -- Baptism and the Lord's Supper -- The Church -- The Great Crowd -- Creation -- Bible chronology and eschatological prophecy -- The Resurrection -- The sacredness of life and blood -- The preaching work -- pt. III. Organization and community -- 10. Organizational structure -- The Witness hierarchy -- The development of the governing body -- Governing body committees -- The world-wide headquarters -- The legal corporations -- Watch Tower wealth -- Watchtower literature -- Zone, district, and circuit overseers -- Branches -- Elders and ministerial servants -- Pioneers -- Congregational meetings -- Evangelism -- Formal organizational controls -- Informal controls -- Organizational efficiency -- 11. The witness community -- Membership, recruitment, and conversion -- Sex, marriage, and the family -- Education -- Entertainment, the arts, and literature -- Moral values and social relationships -- Moral behavior -- Ethnic and racial attitudes -- Witness mental health -- Decreasing zeal -- Dissonance and dissent -- Response to dissent -- The effects of Watchtower policy -- Witness instability and conservatism -- Conclusion.
Includes bibliographical references (pages 475-507) and index.
Keywords: Jehovah's Witnesses; Watch Tower Bible and Tract Society of Pennsylvania